Analisis Sosial Ekonomi Peternakan Sapi Bali Gaduhan Terhadap Perkembangan Tinggi Gumba Ternak Setelah Dua Tahun Pemeliharaan - Herlinae Herlinae; Yemima Yemima; Dedi Asandi Jaya (Fakultas Peternakan Universitas Kristen Palangka Raya, 2012)
The study aims to determine socio economic full inkind Bali cattle rancher to high development Gumba livestock after 2(two) years to receiving assistance. The study was conducted by surveying,interview by made spreading a structured questionnaire. Socio economic variabels are progress of goat livestock, age, education, revenue, and knowledge of farming. Sample 16 respondents who received Bali cattle in 2010 in the Village Hamlet South lake District Ganting South Barito Regency. Analysis of data by multiple linear regression statistical test with the level test(a)=0,05. Statistical data processing using a computer program SPSS version 17. The result was most of the respondent in the category of medium knowledge about cattle raising system. Socio economic variables such as variable breeder age, education, revenue, and knowledge does not effect on the development of high Gumba Bali Cattle.